Clinical characteristics of late-onset neuromyelitis optica spectrum disorder: A multicenter retrospective study in Korea. (November 2017) - Seok, Jin Myoung; Cho, Hye-Jin; Ahn, Suk-Won; Cho, Eun Bin; Park, Min Su; Joo, In-Soo; Shin, Ha Young; Kim, Sun-Young; Kim, Byung-Jo; Kim, Jong Kuk; Cho, Joong-Yang; Huh, So-Young; et al.
Background: There are currently few studies regarding late-onset neuromyelitis optica spectrum disorder (LO-NMOSD). Objective: We aimed to describe the characteristic features of patients with LO-NMOSD in Korea. Methods: Anti-aquaporin-4 antibody-positive patients with neuromyelitis optica spectrum disorder (NMOSD) from nine tertiary hospitals were reviewed retrospectively. The patients were divided into two groups based on age of onset: LO-NMOSD (⩾50 years of age at onset) versus early-onset neuromyelitis optica spectrum disorder (EO-NMOSD) (<50 years of age at onset). Clinical, laboratory, and magnetic resonance imaging (MRI) parameters were investigated. Results: Among a total of 147 patients (125 female; age of onset, 39.4 ± 15.2 years), 45 patients (30.6%) had an age of onset of more than 50 years. Compared to patients with EO-NMOSD, patients with LO-NMOSD had more frequent isolated spinal cord involvement at onset (64.4% vs 37.2%, p = 0.002), less frequent involvement of the optic nerve (40.0% vs 67.7%, p = 0.002), and less frequent brain MRI lesions (31.1% vs 50.0%, p = 0.034). Furthermore, there was a significant positive correlation between age of onset and Expanded Disability Status Scale (EDSS) score at last follow-up ( r = 0.246, p = 0.003). Conclusion: Age of onset could be an important predictor of lesion location and clinical course of patients with NMOSD.